Nonerythropoietic Erythropoietin Mimetic Peptide ARA290 Ameliorates Chronic Stress-Induced Depression-Like Behavior and Inflammation in Mice - Xu, Guanglei; Zou, Tao; Deng, Lijiao; Yang, Guang; Guo, Tingting; Wang, Yi; Niu, Chunxiao; Cheng, Qianqian; Yang, Xiqin; Dong, Jie; Zhang, Jiyan (Frontiers in Pharmacology, 2022)
Major depressive disorder (MDD) is a highly prevalent psychiatric disorder. But the treatment of depression remains challenging. Anti-inflammatory treatments frequently produce antidepressant effects. EPO-derived helix-B peptide ARA290 has been reported to retain the anti-inflammatory and tissue-protective functions of EPO without erythropoiesis-stimulating effects. The effects of ARA290 on MDD remain elusive. This study established chronic unpredictable mild stress and chronic social defeat stress mouse models. Daily administration of ARA290 during chronic stress induction in two mouse models ameliorated depression-like behavior, similar to fluoxetine. With marginal effects on peripheral blood hemoglobin and red cells, ARA290 and fluoxetine reversed chronic stress-induced increased frequencies and/or numbers of CD11b+Ly6Ghi neutrophils and CD11b+Ly6Chi monocytes in the bone marrow and meninges. Furthermore, both drugs reversed chronic stress-induced microglia activation. Thus, ARA290 ameliorated chronic stress-induced depression-like behavior in mice through, at least partially, its anti-inflammatory effects.